Black utopias : speculative life and the music of other worlds - Brown, Jayna, 1966- (Duke University Press, 2021)
"In Black Utopias Jayna Brown looks to utopia as a way of exploring new states of being, doing, and imagining in Black culture. Brown uses the lives and work of Black women mystics Sojourner Truth and Rebecca Cox Jackson, musicians Alice Coltrane and Sun Ra, and speculative fiction writers Samuel Delany and Octavia Butler to develop a concept of utopia that radically refuses the terms of liberal humanism. For Brown, utopia consists of those moments in the here and now when Black people—untethered from the hope of rights, recognition, or redress—celebrate themselves as elements in a cosmic effluvium. In such moments, musical, literary, and mystic practices become utopian enclaves in which Black people can take part in modes of alternative worldmaking. Brown demonstrates that engaging in such practices gives Black people the power to destabilize humanism and to create new genres of existence and models of collectivity"--Publisher's description.